Management of Auxiliary Personnel at the Education, Youth, and Sports Office of the Special Region of Yogyakarta - Rejokirono, Rejokirono; Maryono, Maryono; Nugroho, Agung (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study analyzes the Management of auxiliary Personnel within the Department of Education, Youth, and Sports (Disdikpora) of the Special Region of Yogyakarta (DIY). Employing a qualitative approach through a case study method, data were gathered via interviews, observations, and documentation. Research informants comprised structural and functional officials within Disdikpora DIY and auxiliary Personnel from various operational units. Findings indicate that the Management of auxiliary Personnel within the Disdikpora DIY has been effectively established, encompassing planning, organization, implementation, and supervision/evaluation. Supporting factors include the involvement of various stakeholders, legal frameworks, official decrees, supportive leadership policies, opportunities for external collaborations, and cooperation between civil servants (PNS) and auxiliary Personnel. Despite encountering several challenges, measures have been taken to address them. Improvement needs to encompass regulatory adjustments, including gubernatorial regulations within DIY, welfare considerations, diploma adjustments, position qualifications, and job descriptions of auxiliary Personnel.